Location of residence associated with the likelihood of patient visit to the preoperative assessment clinic - Lemaire Jane B; Pocobelli Gaia; Beck Cynthia A; Seidel Judy E; Bugar Jennifer M; Quan Hude; Ghali William A (BMC, 2006)
Abstract Background Outpatient preoperative assessment clinics were developed to provide an efficient assessment of surgical patients prior to surgery, and have demonstrated benefits to patients and the health care system. However, the centralization of preoperative assessment clinics may introduce geographical barriers to utilization that are dependent on where a patient lives with respect to the location of the preoperative assessment clinic. Methods The association between geographical distance from a patient's place of residence to the preoperative assessment clinic, and the likelihood of a patient visit to the clinic prior to surgery, was assessed for all patients undergoing surgery at a tertiary health care centre in a major Canadian city. The odds of attending the preoperative clinic were adjusted for patient characteristics and clinical factors. Results Patients were less likely to visit the preoperative assessment clinic prior to surgery as distance from the patient's place of residence to the clinic increased (adjusted OR = 0.52, 95% CI 0.44-0.63 for distances between 50-100 km, and OR = 0.26, 95% CI 0.21-0.31 for distances greater than 250 km). This 'distance decay' effect was remarkable for all surgical specialties. Conclusion The present study demonstrates that the likelihood of a patient visiting the preoperative assessment clinic appears to depend on the geographical location of patients' residences. Patients who live closest to the clinic tend to be seen more often than patients who live in rural and remote areas. This observation may have implications for achieving the goals of equitable access, and optimal patient care and resource utilization in a single universal insurer health care system.